2014
DOI: 10.1002/ar.22977
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Study of the Facial Canal Using Microcomputed Tomography for Improved Anatomical Comprehension

Abstract: The aims of this study were to determine the various dimensions of the normal facial canal and to identify the spatial relationships between the facial canal and its adjacent structures using microcomputed tomography (micro-CT) imaging and three-dimensional (3D) reconstruction. The petrous parts of 54 temporal bones were scanned using micro-CT with a slice thickness of 35 lm. The serial micro-CT images were used to reconstruct 3D volumes of the facial canal and the bony labyrinth with the aid of computer softw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…The compression of an inflamed facial nerve has previously been explained on the basis of irregularity between the lumen size of the un-yielding facial canal and the neve width [11,12]. However the sporadic reports on the variation of size and shape of the stylomastoid foramen [13,14], which can also have clinical implications in unexplained cases of facial nerve palsy, have never been discussed with regards to compression of the nerve. Hence the present study was conducted with an objective to study the variations in size and shape of the stylomastoid foramen in dry adult human skulls.…”
Section: Introductionmentioning
confidence: 99%
“…The compression of an inflamed facial nerve has previously been explained on the basis of irregularity between the lumen size of the un-yielding facial canal and the neve width [11,12]. However the sporadic reports on the variation of size and shape of the stylomastoid foramen [13,14], which can also have clinical implications in unexplained cases of facial nerve palsy, have never been discussed with regards to compression of the nerve. Hence the present study was conducted with an objective to study the variations in size and shape of the stylomastoid foramen in dry adult human skulls.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we applied microtomography to obtain reconstructed objects with a resolution of 18 µm, which appeared accurate enough to visualize the facial canal morphology and its course in a three-dimensional manner. This imaging modality was used in only a few studies to present the overall course and morphology of the facial canal but not its structural defects [16, 17]. Although micro-CT is excellent for visualizing morphological aspects of the osseous defects of the facial canal, computed tomography still remains the fundamental technique for imaging facial canal anatomy in preoperative practice [8].…”
Section: Discussionmentioning
confidence: 99%
“…Bell's palsy (BP) is the commonest cause of facial paralysis. While it is currently idiopathic by definition, virally mediated inflammation is widely accepted as the foremost etiological factor 1,2 . It has also been suggested that the anatomy of the facial nerve canal might play an important causative role.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that the anatomy of the facial nerve canal might play an important causative role. In particular, neural inflammation within the narrow portions of the facial nerve canal is presumed to result in neural impingement 1‐4 . This is most relevant at the labyrinthine portion and its meatal foramen, where the facial nerve canal is at its narrowest 2,4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation